2016
DOI: 10.5352/jls.2016.26.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Gene Interaction and Anthocyanin Biosynthesis of Purple Pericarp Trait for Yield Improvement in Black Rice

Abstract: Rice (Oryza sativa L.) is one of the major cereal crops for consumption by the world's population. Recently, various colored rice, such as white, red, brown, green, and black rice, have caught the attention of world consumers. The commercial name 'black rice' contains a high amount of anthocyanins in pericarp, which increases nutritional value. Moreover, anthocyanin in black rice possesses biomedical properties, including anti-oxidant, anti-cancer, and anti-inflammatory effects in humans. In genetics, black ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…We confirmed that the quantity of C3G and P3G maximally accumulated in the seeds of Heuknam and Heukseol, black rice cultivars, at around 20 DAH (Lee et al, unpublished), which corresponds to a previous report [57], and collected developing seeds of Dongjin, Geonganghongmi, Jeokjinju, Boseokheukchal, Heukjinju, Heukjinmi, and Heukseol at 20 DAH for gene expression analysis. To check the overall expression patterns of genes putatively involved in the biosynthetic pathway of anthocyanins, including bHLH [21,45], MYB [20,58], WD40 [59], PAL [22], C4H [23,24], 4CL [25], CHS [26,27], CHI [28][29][30], F3H [31,32], F3´H [36,37], DFR [33][34][35], and ANS [39][40][41], and other genes indirectly related to the biosynthetic pathway of anthocyanins, including HCT [60], CCR [61,62], CAD [63], and LAR [64], in developing seeds of white, red, and/or black rice at 20 DAH, only one replicate of total RNA samples of Dongjin, Jeokjinju, or Heukseol was chosen for RNA-seq through Illumina sequencing.…”
Section: Genes Involved In the Biosynthetic Pathway Of Anthocyanins D...supporting
confidence: 88%
“…We confirmed that the quantity of C3G and P3G maximally accumulated in the seeds of Heuknam and Heukseol, black rice cultivars, at around 20 DAH (Lee et al, unpublished), which corresponds to a previous report [57], and collected developing seeds of Dongjin, Geonganghongmi, Jeokjinju, Boseokheukchal, Heukjinju, Heukjinmi, and Heukseol at 20 DAH for gene expression analysis. To check the overall expression patterns of genes putatively involved in the biosynthetic pathway of anthocyanins, including bHLH [21,45], MYB [20,58], WD40 [59], PAL [22], C4H [23,24], 4CL [25], CHS [26,27], CHI [28][29][30], F3H [31,32], F3´H [36,37], DFR [33][34][35], and ANS [39][40][41], and other genes indirectly related to the biosynthetic pathway of anthocyanins, including HCT [60], CCR [61,62], CAD [63], and LAR [64], in developing seeds of white, red, and/or black rice at 20 DAH, only one replicate of total RNA samples of Dongjin, Jeokjinju, or Heukseol was chosen for RNA-seq through Illumina sequencing.…”
Section: Genes Involved In the Biosynthetic Pathway Of Anthocyanins D...supporting
confidence: 88%
“…The AL phenotype is common in black rice because the mutated OsB2 overlaps the function of OsRb and functional OsDFR alleles are required. However, anthocyanin accumulation in the leaf is not a favourable trait because it negatively affects yield potential (Rahman et al ., ). Rice breeders do not have an effective approach to remove the anthocyanin pigments in leaves without influencing the anthocyanin content in the pericarp because the tissue‐specific regulatory mechanism of anthocyanin biosynthesis in rice has not been characterized.…”
Section: Resultsmentioning
confidence: 97%
“…The stark colour contrasts between coloured rice and viands (except for braised meats, which mostly have dark sauces, and for risotto, still a foreign concept) may also turn consumers off. However, unmilled rice is known to contain more nutrients and fibre than milled rice ( Trinidad et al, 2013 , Villareal et al, 1991 ), while dark pigments in the bran are associated with biomedical properties (reviewed in Rahman et al, 2016 ). The experts, therefore, must have included health-improving properties in defining premium rice.…”
Section: Resultsmentioning
confidence: 99%